2022
DOI: 10.1155/2022/4056713
|View full text |Cite|
|
Sign up to set email alerts
|

Assessment of Ecological Environment Quality for Urban Sustainable Development Based on AHP

Abstract: Cities are gradually developed on the basis of adapting and transforming the natural environment. In a certain urban area, human activities, natural environment, and other factors and their mutual influence constitute the urban ecological environment. Therefore, the evaluation of urban ecological environment quality is of great significance to the analysis of urban development. This paper takes a city in Western China as the evaluation object, uses AHP to determine the index weight, reasonably analyzes the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The composition of the urban ecological environment results from the interaction between human activities and the natural environment [1]. With the acceleration of urbanization, compared with rural areas, the landscape in urban areas is more complex and mottled [2].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the urban ecological environment results from the interaction between human activities and the natural environment [1]. With the acceleration of urbanization, compared with rural areas, the landscape in urban areas is more complex and mottled [2].…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%